Magie in den älteren und jüngeren Runeninschriften? – Zum Status magischer Konzepte in der Runologie - Michael Schulte (Filologia Germanica)
To what extent can individual runic inscriptions or inscription groups of the older and younger period be classified as ‚magical‘ or ‚profane‘? The present article scrutinizes Elmer Antonsen’s anti-magical approach to the older runic inscriptions and offers a more nuanced view, which rejects the basic assumption that inscriptions are solely profane, devoid of sacred and/or magical functions. Magical inscriptions are defined in this paper as those runic artefacts which deliberately exert influence on higher or lower powers, such as gods, helping spirits or evil spirits. Methodologically, three examples of the older and younger runic inscriptions are selected, which combine several functional elements that can be interpreted as magical: the Kylver stone (KJ 1), the Vedslet sandstone amulet (DR 57), and the gravestone of Gørlev (DR 239). This last has at least three such functional elements: a fuþark inscription, a grave formula, and the so-called thistle- mistle formula. This article addresses not only the allegedly magical functions of the fuþark as a whole, but also the magical use of individual runes and runic names; compare the ideographic use of positively charged runes such as 2 j (= *jāra n. ‚year, good harvest‘) and F f (= *fehu n. ‚cattle, wealth‘). On the basis of these case studies, the question of rune magic in the North will be further pursued.